Cross-sectional analysis of clinical aspects in patients with long-COVID and post-COVID syndrome - Schulze, Hannah; Charles James, Jeyanthan; Trampe, Nadine; Richter, Daniel; Pakeerathan, Thivya; Siems, Nadine; Ayzenberg, Ilya; Gold, Ralf; Faissner, Simon (Frontiers in Neurology, 2022)
Objective Regarding pathogenesis, clinical manifestations, at-risk individuals, and diagnostic methods for stratifying patients for therapeutic approaches, our understanding of post-COVID syndrome is limited. Here, we set out to assess sociodemographic and clinical aspects in patients with the long-COVID and post-COVID syndrome. Methods We performed a cross-sectional analysis of patients presenting at our specialized university hospital outpatient clinic. We assessed patients' clinical presentation, fatigue, symptoms of depression and anxiety, and impairment of smell. Results A total of 101 patients were included (73.3% female), of whom 78.2% had a mild course of COVID-19. At presentation, 93.1% suffered from fatigue, 82.2% from impaired concentration, and 79.2% from impaired memory, 53.5% had impaired sleep. The most common secondary diagnosis found in our cohort was thyroid disease. Fatigue analysis showed that 81.3% of female and 58.8% of male patients had severe combined fatigue. Female gender was an independent risk factor for severe fatigue (severe cognitive fatigue OR = 8.045, p = 0.010; severe motor fatigue OR = 7.698, p = 0.013). Males suffered from more depressive symptoms, which correlated positively with the duration of symptom onset. 70.3% of patients with anamnestic smell impairment had hyposmia, and 18.9% were anosmic. Interpretation Most long-COVID patients suffered from severe fatigue, with the female sex as an independent risk factor. Fatigue was not associated with symptoms of depression or anxiety. Patients with long-COVID symptoms should receive an interdisciplinary diagnostic and therapeutic approach depending on the clinical presentation.